Taking Europe to its extremes: Examining cueing effects of right-wing populist parties on public opinion regarding European integration - Catherine E. Netjes; Erica Edwards (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
In this article we examine the role of right-wing parties in framing and mobilizing national identity against European integration. Using a multi-level analysis and combining individual-level and contextual data, we analyze public support for European integration within the Western European member states of the European Union from 1992 to 2002. The empirical analysis shows that national identities are contested and constructed within national contexts and that right-wing populist elites act as influential political cues in this process. Populist political entrepreneurs on the right side of the political spectrum play a decisive role in framing opposition to supranational governance with defense of the national community. – – In diesem Papier untersuchen wir die Rolle rechter Parteien bei der Gestaltung nationaler Identität und ihrer Mobilisierung gegen die europäische Integration. Mit Hilfe einer Mehrebenenanalyse und der Kombination von Daten auf der individuellen und der kontextuellen Ebene, analysieren wir die öffentliche Unterstützung für die europäische Integration in den westeuropäischen Mitgliedsstaaten der Europäischen Union von 1992 bis 2002. Die empirische Untersuchung zeigt, dass nationale Identitäten im nationalen Kontext ausgefochten und herausgebildet werden und dass rechte populistische Eliten in diesem Prozess als einflussreiche politische Signalgeber fungieren. Populistische politische Entrepreneurs auf der rechten Seite des politischen Spektrums spielen eine entscheidende Rolle bei der Herausbildung einer Opposition zur supranationalen Regierung im Namen der Verteidigung der nationalen Gemeinschaft.
Keywords: 300